MARKET STRUCTURE IN ISLAMIC PERSPECTIVE: A CRITICAL EXAMINATION OF THE TERMS PERFECT AND IMPERFECT COMPETITION - Ninglasari, Sri Yayu; Himmawan, M. Fikri; Rosyidi, Luthfi Nur; Asyiah, Aas Nur (Universitas Muhammadiyah Surabaya, 2023)
The purpose of this study is to examine the terms